Improvement Empty Fruit Bunch Properties through Torrefaction - Thuraiya, Thaim; Ruwaida, Abdul Rasid (AENSI Publishing, 2016)
The world is currently facing challenges to reduce dependence on fossil fuels and to achieve a sustainable and renewable energy supply. With environmental issues associated with conventional fossil-based fuels such as the release of the greenhouse gases, more researchers are turning to find alternatives, and this leads to applying biomass waste as one of the renewable energy source. However, there are setbacks in utilizing the biomass waste directly, such as it having high moisture content, and low energy density. This can be overcome through torrefaction, which is a thermal pre-treatment technique at temperatures ranging from 200 – 300oC. The aim of this work is to improve the biomass waste properties through torrefaction. In this study, the oil palm Empty Fruit Bunch (EFB) was examined, and its properties were characterized based on severe torrefaction temperatures (280, 300 and 320oC) and at various residence time (30, 60 and 90 minutes). The results revealed that the torrefaction temperature have significant effect the mass yield and high heating value of EFB. At temperature 320oC and 30 minutes’ residence time, the mass yield was 57.97% and the high heating value (HHV) was 22.10 MJ/kg. This is an improvement as the HHV of the torrefied EFB was 27.31% higher than that of the raw EFB. This can be observed at temperature 280oC, when the residence time was prolonged, there was insignificant increase in mass yield. Increasing the residence time results in only a slight increment for all of the severe torrefaction temperature. This suggests that the 30 minutes’ residence time is sufficient, and prolonged exposure to the torrefaction temperature will not affect the physical properties of the torrefied biomass. This study has highlighted the potential of EFB as one of the feedstock for energy production process through thermal treatment.